Discrimination and sexual risk among Caribbean Latinx young adults. Issue 5 (3rd July 2020) - Otiniano Verissimo, Angie Denisse; Dyer, Typhanye Penniman; Friedman, Samuel R.; Gee, Gilbert C.
ABSTRACT: Objectives: Discrimination, such as being treated unfairly due to race, contributes to stress. Individuals may cope with this by engaging in risky behaviors. Consistent with this premise, prior studies found that discrimination is associated with substance use. Research has also shown that sex while 'high' on alcohol and drugs is associated with increased risk for HIV and other STIs. The present study examines the relationship between discrimination and sexual risk. We investigate whether discrimination is associated with sex while high on alcohol and drugs. Design: Analyses focus on a sample of 356 Caribbean Diasporic young adults, primarily Caribbean Latinx, aged 18 to 25 who participated in the Drug Use and HIV Risk among Youth Survey carried out from 1997 to 2000 in Brooklyn, New York. Logistic regression examined the association between self-reported discrimination and sex while high. Results: More than half (52.3%) of respondents reported moderate discrimination. Sex while high was also reported: 35.7% for alcohol, 43.3% for marijuana, and 32.6% for heroin/cocaine. Discrimination was associated with increased risk of sex while high on (1) marijuana and (2) heroin/cocaine, but was not with alcohol. Conclusions: Discrimination may be a risk factor for engaging in sex while high on drugs, which may put individuals at risk for HIV as well as other STIs . Future research should explore relationships between discrimination and sex while high on alcohol and drugs among various racial/ethnic groups and Diasporas, while also assessing how this relationship may contribute to HIV incidence.